Brain drain in globalization: a general equilibrium analysis from the sending countries' perspective - Luca Marchiori; I-ling Shen; Frédéric Docquier (Institute for the Study of Labor (IZA), 2009)
The paper assesses the global effects of brain drain on developing economies and quantifies the relative sizes of various static and dynamic impacts. By constructing a unified generic framework characterized by overlapping-generations dynamics and calibrated to real data, this study incorporates many direct impacts of brain drain whose interactions, along with other indirect effects, are endogenously and dynamically generated. Our findings suggest that the short-run impact of brain drain on resident human capital is extremely crucial, as it does not only determine the number of skilled workers available to domestic production, but it also affects the sending economy's capacity to innovate or to adopt modern technologies. The latter impact plays an important role particularly in a globalized economy where capital investments are made in places with higher production efficiencies ceteris paribus. Hence, in spite of several empirically documented positive feedback effects, those countries with high skilled emigration rates are the most candid victims to brain drain since they are least likely to benefit from the brain gain effect, and thus suffering from declines of their resident human capital.
urn:nbn:de:101:1-2009061926
Keywords: F22; J24; O15; 330; Brain drain; capital flow; development; human capital; remittances; Brain Drain; Humankapital; Brain Drain; Entwicklung; Allgemeines Gleichgewicht; Kapitalmobilität; Rücküberweisung (Migranten); Theorie; Entwicklungsländer